IDDF2020-ABS-0190 Efficacy of infliximab treatment on the mucosal healing of different intestinal segments in patients with ileocolonic Crohn's disease. (18th November 2020) - Wu, Yaling; Zhang, Lei; Cao, Jingli; Wang, Haichao; Ye, Chen; Zhuoma, Deji; Yang, Pengyu; Wang, Xiaolei
Abstract : Background: Mucosal healing (MH) is the key aim of the treat-to-target strategy for patients with Crohn's disease (CD). The efficacy of infliximab on MH in different ileocolonic segments is unclear. The aim of this study was to investigate endoscopic MH in different ileocolonic segments in patients with CD who received infliximab treatment. Methods: A retrospective, single-center study was performed in patients with active ileocolonic CD between January 2012 and December 2018. All patients underwent IFX treatment for at least 30 weeks. The MH of five ileocolonic segments was assessed by the Simple Endoscopic Score for CD (SES-CD) at baseline, week 14 and week 30. The SES-CD scores were analyzed by a mixed-effects model after the confounding factors were corrected. Results: A total of 101 eligible patients were included. The baseline endoscopic severity was similar across segments. At week 30, the greatest changes in SES-CD ulcer size and ulcerated surface were -94.29% and -94.32% both in the transverse colon ( P <0.0001), and the smallest changes were -67.88% and -69.67% both in the terminal ileum ( P <0.0001) compared with the changes in the other segments. Stenosis mainly presented in the right colon (12/29, 41.38%). The change in SES-CD stenosis was -6.25% in the right colon at week 30 compared with -71.88% at week 14 (P=0.0030). At week 30, the transverse colon achieved the highest rate of complete MH (CMH) with 81.2%, and the lowest CMH rate occurred in the terminal ileum with 45.6%. Conclusions: Ileocolonic segments in Crohn's disease presented different endoscopic MH during IFX treatment. The transverse colon showed the highest MH rate, whereas the right colon had poor improvement in stenosis even underwent long-term IFX therapy.